PERUBAHAN POLA CURAH HUJAN DI KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN (TAHUN 2003 - 2012) - Yani, Zulhijah Defitri; Edial, Helfia; Farida, Farida (Pendidikan Geografi, 2013)
The research was based on a different pattern of rainfall in the Distric t XI Tarusan Koto. The result of  this study reveals the magnitude of the average rainfall that occurred in District XI Tarusan Koto in the period 2003-2012 as well as changes in rainfall patterns.This  research  used  descriptive  quantitative  method  for  processing  of  secondary  data. Quantitative descriptive research is to conduct secondary data description of the data and then perform  data  analysis  to  obtain  conclusions.  This  research  area  is  Koto  XI  Tarusan,  South Coastal  District.  The  research  data  was  taken  from  the  station  BMKG  Regional  Sicincin  and PSDA West Sumatra province. Of all the data taken on average  of 10 years  from 2003 to 2012 from  of  three  point  of  observation  post  located  in  Koto  XI  Tarusan,  Nanggalo  Tarusan,  and Duku.The  results  showed  that  :  1)  The  average  rainfall  in  the  2003-2012  observation  period ranged  from  2749.3  to  3136.3  mm  /  year  and  (2)  the  rainfall  in  the  sub  District  Tarusan, equatorial rainfall  pattern obtained with bimodal shape ( two peak rainfall  ), where low rainfall occurred  in  January-June,  while  the  high  rainfall  occurred  in  August-December.  Of  the  three rainfall stations, there are no changes in rainfall patterns mean.